Implications of circular strategies on energy, water, and GHG emissions in informal housing in Lima - Sarmiento Pastor, Jaime Miguel (2025)
Informal and self-built housing developments worldwide are expanding rapidly, often following incremental construction phases that drive substantial resource demands and emissions as communities consolidate. In Lima, Peru, informal settlements exemplify this trend, revealing significant environmental impacts as progressive construction intensifies urban growth. Informal housing construction in Lima progresses through four key stages: Inception, Development, Completion, and Consolidation, each characterized by material additions and upgrades that increase embodied environmental impacts over time and across all life cycle phases. A Life Cycle Assessment (LCA) was applied to evaluate total greenhouse gas (GHG) emissions, water use, and fossil energy consumption across these four building consolidation stages. Additionally, three end-of-life scenarios—landfilling, recycling, and selective deconstruction were analyzed to assess the potential benefits of adopting a circular model in construction material use. The results show that the inception stage emits 1.6 Mt(CO2-eq), the development stage 23.15 Mt(CO2-eq), the completion stage 100 Mt(CO2-eq), and the consolidation stage 58 Mt(CO2-eq), totaling 183 Mt(CO2-eq). Due to lower average occupation density, informal housing emits approximately 450 % more GHG emissions per person than its formally constructed counterpart. The linear construction model exacerbates these impacts by generating substantial waste and requiring continual extraction of new materials. Selective deconstruction could reduce carbon emissions by 81 %, water use by 82 %, and fossil energy use by 80 % compared to landfilling. Recycling offers smaller reductions of 69 %, 68 %, and 67 %, respectively. These findings highlight the environmental benefits of integrating circular economy strategies and the need for sustainable material management policies in rapidly urbanizing areas.